Real-time optical monitoring of the dip coating process - Michels, A. F.; Menegotto, T.; Grieneisen, H. P.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Horowitz, F. (Spie - Int Soc Optical Engineering, 2004)
A significant part of film production by the coating industry is based on wet bench processes, where better understanding of their temporal dynamics could facilitate control and optimization. In this work, in situ laser interferometry is applied to study properties of flowing liquids and quantitatively monitor the dip coating batch process. Two oil standards Newtonian, non-volatile, with constant refractive indices and distinct flow properties - were measured under several withdrawing speeds. The dynamics of film physical thickness then depends on time as t(-1/2), and flow characterization becomes possible with high precision (linear slope uncertainty of +/-0.04%). Resulting kinematic viscosities for OP60 and OP400 are 1,17 +/- 0,03. St and 9,9 +/- 0,2 St, respectively. These results agree with nominal values, as provided by the manufacturer. For more complex films (a multi-component sol-gel Zirconyl Chloride aqueous solution) with a varying refractive index, through a direct polarimetric measurement, allowing also determination of the temporal evolution of physical thickness (uncertainty of +/- 0,007 microns) is also determined during dip coating.
Keywords: optical monitoring; interferometry; dip coating; thin films; in situ; real time; refractive index; newtonian oils; sol-gel; flow characterization; viscosimetry